2016
DOI: 10.1111/tpj.13256
|View full text |Cite
|
Sign up to set email alerts
|

Distinct roles of the histone chaperones NAP1 and NRP and the chromatin‐remodeling factor INO80 in somatic homologous recombination in Arabidopsis thaliana

Abstract: Homologous recombination (HR) of nuclear DNA occurs within the context of a highly complex chromatin structure. Despite extensive studies of HR in diverse organisms, mechanisms regulating HR within the chromatin context remain poorly elucidated. Here we investigate the role and interplay of the histone chaperones NUCLEOSOME ASSEMBLY PROTEIN1 (NAP1) and NAP1-RELATED PROTEIN (NRP) and the ATP-dependent chromatin-remodeling factor INOSITOL AUXOTROPHY80 (INO80) in regulating somatic HR in Arabidopsis thaliana. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 84 publications
(191 reference statements)
0
43
1
Order By: Relevance
“…ChIP assays have revealed that the increase in gene expression occurs concomitantly with the increase in H3K4me3 levels, particularly around the TSS and gene bodies, without changes in the DNA methylation levels [115]. The gene expression changes in response to DNA damage are not affected, even after knocking out the six genes encoding NAP1 and NRP histone chaperones [116]. This indicates that they participate downstream in the pathway, probably during nucleosome remodeling associated with DNA repair.…”
Section: Genome Replication and Chromatin Silencingmentioning
confidence: 99%
See 1 more Smart Citation
“…ChIP assays have revealed that the increase in gene expression occurs concomitantly with the increase in H3K4me3 levels, particularly around the TSS and gene bodies, without changes in the DNA methylation levels [115]. The gene expression changes in response to DNA damage are not affected, even after knocking out the six genes encoding NAP1 and NRP histone chaperones [116]. This indicates that they participate downstream in the pathway, probably during nucleosome remodeling associated with DNA repair.…”
Section: Genome Replication and Chromatin Silencingmentioning
confidence: 99%
“…This indicates that they participate downstream in the pathway, probably during nucleosome remodeling associated with DNA repair. It has been shown that NAP1 and NRP are required to trigger homologous recombination (HR) before chromatin is remodeled at damaged sites, once γ-H2A.X foci are formed and in an INO80-dependent manner [116]. Recent results show that NRP1 accumulates in chromatin after DNA damage and binds cytochrome c [117] through the NRP1 histone-binding domain [118].…”
Section: Genome Replication and Chromatin Silencingmentioning
confidence: 99%
“…NAP1;1-3 proteins are ubiquitously expressed, form homodimers and heterodimers and localize abundantly to the cytoplasm (Liu et al, 2009). NAP1;4 encodes a shorter protein lacking canonical sequences and is only weakly expressed in roots and pollen grains (Liu et al, 2009; Zhou et al, 2016). Loss-of-function mutations of individual NAP1 genes do not affect plant growth and development under standard laboratory conditions (Gao et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…NRP s are related to the yeast VACUOLAR PROTEIN SORTING (Vps75 and human SET/TAF proteins and participate in nucleosome assembly and histone binding (Zhu et al, 2006; Tang et al, 2008; Bowman et al, 2011; Bowman et al, 2014; Kumar et al, 2019). NAP1 and NRPs act in a synergetic molecular pathway to regulate HR, however, there is a lack of information on which step/s of it they participate in (Zhu et al, 2006; Zhou et al, 2016). The multiple mutants of nap1;1-4nrp1-2 are largely sensitive to genotoxic stress, but are otherwise viable (Zhou et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation